Legal Protection In Road Transportation: Safety, Passenger Rights And Carrier Liability - Fitri Arianti Saputri (Leges Privatae, 2024)
Road transport is one of the main modes of transportation worldwide, with millions of people and goods being transported every day. This article discusses the legal protections put in place in this transportation context, focusing on passenger safety, passenger rights, and carrier responsibilities for goods. Although the legal framework has been established, there are still challenges in its implementation, such as the level of non-compliance with safety rules. In addition, this article highlights the importance of increased cooperation between the government and transporters to improve legal protection for all parties involved. Improvement and enhancement measures are needed for legal protection to be more effective and comprehensive in safeguarding the safety and welfare of passengers and goods transported by road.